Taxonomic revision of West-Alpine cushion plant species belonging to Androsace subsect. Aretia - Dentant, Cédric; Lavergne, Sébastien; Malécot, Valéry (Botany letters, 2018)
High-altitude rockjasmines (genus Androsace) are a paramount example of evolutionary radiations in temperate mountains of the Northern Hemisphere. Yet, we show here that their taxonomy is incomplete and has been subject to many historical mistakes, probably due to the lack of exploration of mountains by the classical botanists who described these species. Here we wish to clarify the application of names with regard to four defined morphotypes, typical of high-elevation zones of the Western Alps, in order to set a definitive basis for morphological delimitation of a likely new species discovered in the Mont Blanc range (species not described in this work). To do so, we review the historical taxonomic treatments and positions, carefully reconsider types and species names for these morphotypes, and designate lectotypes and epitypes for each of them. In particular, we confirm the validity of names commonly used to refer to the taxa Androsace alpina, Androsace helvetica, and Androsace pubescens. We show that Androsace vandellii is an invalid name and that Androsace argentea should be used instead. Our work illustrates the utility of historical herbaria to clarify the taxonomy of complex groups of plants growing in inaccessible environments such as high-altitude regions.